2014
DOI: 10.1039/c4cp03605k
|View full text |Cite
|
Sign up to set email alerts
|

Promising anchoring groups for single-molecule conductance measurements

Abstract: The understanding of the charge transport through single molecule junctions is a prerequisite for the design and building of electronic circuits based on single molecule junctions. However, reliable and robust formation of such junctions is a challenging task to achieve. In this topical review, we present a systematic investigation of the anchoring group effect on single molecule junction conductance by employing two complementary techniques, namely scanning tunneling microscopy break junction (STM-BJ) and mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
117
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(121 citation statements)
references
References 97 publications
3
117
0
1
Order By: Relevance
“…48 In STM-BJ/MCBJ, single molecules are contacted by two electrodes to form a metal–molecule–metal junction. Under the application of a bias voltage, the current flowing through the molecule, from one electrode to the other is sensitive to the molecular structure (length, conjugation pattern and conformation), 9,10 the chemical nature of the linker which connects the molecule to the electrode, 6,1113 the relative position of linkers attached to the molecular core, 14,15 the binding geometry of molecule between the electrodes, 1618 and the effect of external triggers on molecular structure and environment. 2,6,1922 Thus, these experimental techniques when combined with charge transport theory present a unique opportunity to create dynamic circuits with a library of molecules, which can act like wires, 9,2325 switches 26,27 and diodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…48 In STM-BJ/MCBJ, single molecules are contacted by two electrodes to form a metal–molecule–metal junction. Under the application of a bias voltage, the current flowing through the molecule, from one electrode to the other is sensitive to the molecular structure (length, conjugation pattern and conformation), 9,10 the chemical nature of the linker which connects the molecule to the electrode, 6,1113 the relative position of linkers attached to the molecular core, 14,15 the binding geometry of molecule between the electrodes, 1618 and the effect of external triggers on molecular structure and environment. 2,6,1922 Thus, these experimental techniques when combined with charge transport theory present a unique opportunity to create dynamic circuits with a library of molecules, which can act like wires, 9,2325 switches 26,27 and diodes.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, the conductance of organic molecules utilizing a number of anchoring groups have been compared including benzothiophene (–BT), pyridyl (–PY), amino (–NH 2 ), thiol (–SH), isothiocyanide (–SCN), cyanide (–CN), nitro (–NO 2 ), carboxylic acid (–COOH), dimethyl phosphine (–PMe 2 ), methyl sulphide (–SMe), hydroxyl (–OH), and carbodithiolate based linkers. 6,1113,30 These studies have helped deconvolute the effect of the linkers from that of the molecular core on the single molecular junction conductance. Several experimental and theoretical attempts have been made to understand and/or predict the possible quantum interference patterns which govern the conductance properties of conductance pathways across the molecular core.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, conductance studies with small organic molecules revealed unique correlations between molecular structure and junction conductances. These studies explored the influence of molecular length and conjugation789101112, torsion angle131415, electrode material1617, and anchoring group181920212223, on junction conductance. To date, generic force spectroscopy experiments primarily address supramolecular bonds2425262728, and almost no studies of mechanical properties of covalently-bound junctions were reported4.…”
mentioning
confidence: 99%
“…54,55 Recently, the molecular conductances of Pt(II) complexes trans- Through numerous studies of molecular junctions, the nature of the molecule-electrode contact has proven important, 57 and recognition of the role that anchor groups play in the electrical performance of the junction has led to the development of a wide range of contacting groups and electrode materials. [58][59][60][61][62][63] However, even well-known contacting groups such as thiolates bind to a range of surface sites, including terraces or near to adatoms as well as idealised pristine atomically flat terraces, giving rise to a range of molecular conductance signatures from a given molecular backbone. 64 Consequently, interest has increasingly focussed on molecular junctions in which the molecule is contacted to the electrode by strong electrode-carbon covalent bonds.…”
Section: Introductionmentioning
confidence: 99%